PENGARUH AKTIVITAS BELAJAR DAN KEMANDIRIAN DALAM MENGERJAKAN TUGAS TERHADAP HASIL BELAJAR SISWA EKONOMI KELAS XI DI SMA SEMEN PADANG (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2014)
AbstractThis study aims to examine) The effect of learning activities and independence in doing tasks on learning outcomes of students in high school economics class XI Semen Padang.When the study was conducted in May 2014The results showed that: 1) There is a positive and significant effect of learning activities on student learning outcomes in high school economics class XI Semen Padang this with tcount>t table (4.955> 1.661). 2) in positive and significant impact of independence in doing the learning outcomes of students in high school economics class XI Semen Padang this is evidenced by the value of tcount>ttable (7.556> 1.661), there is a positive and significant impact jointly between learning activities and independence in the tasks of the learning outcomes of students in high school economics class XI Semen Padang academic year 2013/2014 this is evidenced by the Fcount>Ftable (135.599>3.09) and R Square0.745.